2008
DOI: 10.1016/j.canlet.2008.02.069
|View full text |Cite
|
Sign up to set email alerts
|

2′-Deoxy-N4-[2-(4-nitrophenyl)ethoxycarbonyl]-5-azacytidine: A novel inhibitor of DNA methyltransferase that requires activation by human carboxylesterase 1

Abstract: Abstract2'-Deoxy-N4-[2-(4-nitrophenyl) ethoxycarbonyl]-5-azacytidine (NPEOC-DAC), decitabine with a modification of the N4 position of the azacitidine ring can be used to inhibit DNA methyltransferase. This modification protects the azacitidine ring and can be cleaved by carboxylesterase to release decitabine. NPEOC-DAC was 23-fold less potent at low doses (<10 µM) than decitabine at inhibiting DNA methylation, and was also associated with a 3-day delay in its effect. However, at doses ≥ 10 µM NPEOC-DAC was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 37 publications
(43 reference statements)
0
25
0
Order By: Relevance
“…RX-3117 has been approved by the FDA for the treatment of pancreatic cancers. In addition, more nucleoside analogues were designed and studied for their ability to inhibit DNMTs, such as 2-(p-nitrophenyl) ethoxycarbonyl-DAC (NPEOC-DAC), CP-4200, 4'-thio-2'-deoxycytidine (TdCyd), and 5-aza-4'-thio-2'-deoxycytidine (5-aza-T-dCyd) (Patent Numbers WO2009042766, WO2009042767, WO2011109012 and US 20110218170 A1) (Byun et al, 2008;Brueckner et al, 2010;Thottassery et al, 2010;Thottassery et al, 2014) (Table 3). Collectively, these findings suggest we are close to finding low toxicity DNMT-depleting anticancer drugs.…”
Section: Nucleosidic Dna Methylation Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…RX-3117 has been approved by the FDA for the treatment of pancreatic cancers. In addition, more nucleoside analogues were designed and studied for their ability to inhibit DNMTs, such as 2-(p-nitrophenyl) ethoxycarbonyl-DAC (NPEOC-DAC), CP-4200, 4'-thio-2'-deoxycytidine (TdCyd), and 5-aza-4'-thio-2'-deoxycytidine (5-aza-T-dCyd) (Patent Numbers WO2009042766, WO2009042767, WO2011109012 and US 20110218170 A1) (Byun et al, 2008;Brueckner et al, 2010;Thottassery et al, 2010;Thottassery et al, 2014) (Table 3). Collectively, these findings suggest we are close to finding low toxicity DNMT-depleting anticancer drugs.…”
Section: Nucleosidic Dna Methylation Inhibitorsmentioning
confidence: 99%
“…NPEOC-DAC 18499340 (Byun et al, 2008) SGI-110 20442312 (Chuang et al, 2010) CP-4200 20442313 (Brueckner et al, 2010) (Fahy et al, 2009) …”
mentioning
confidence: 98%
“…Because of its dependency on metabolism by carboxylesterase for biologic activity, NPEOC-decitabine can be specifically used to target cancer cells with high expression of carboxylesterase, while other tissues with low levels of the enzyme will not be affected. [115,152] Unfortunately, high levels of carboxylesterase are only observed in hepatic carcinomas, thus restricting the potential of this drug in clinical use to this malignancy. An additional limitation of NPEOC-decitabine is its very low solubility in water, which severely limits its bioavailability.…”
Section: Specific Targetingmentioning
confidence: 98%
“…[115] NPEOC-decitabine requires activation by human carboxylesterase for biologic activity. In the presence of carboxylesterase 1 (CES1), the N4 nitrophenyl group on NPEOC-decitabine is cleaved, resulting in decitabine, which can then be incorporated into the DNA sequence.…”
Section: Specific Targetingmentioning
confidence: 99%
“…151 In vitro studies have demonstrated the ability to cleave this NPEOC group by carboxylesterase enzymes resulting in the production of decitabine. The compound has demonstrated molecular changes in human cancer cell lines as evidenced by decreased global and gene specific methylation, however, this effect was limited to cells expressing carboxylesterase 1.…”
Section: Other Demethylating Agentsmentioning
confidence: 99%